2017
DOI: 10.1007/s12032-017-1070-7
|View full text |Cite
|
Sign up to set email alerts
|

The novel role of IL-37 in prostate cancer: evidence as a promising radiosensitizer

Abstract: Prostate cancer (PCa) is the most common non-cutaneous cancer in men in the USA. Radiation therapy (RT) is widely considered the standard treatment for PCa. IL-37 is an IL-1 family member, and it has been extensively studied in immunity. However, no studies have been done regarding its potential as a radiosensitizer. This study is designed to investigate the direct effect of IL-37 on growth of DU145 and PC-3, two widely studied PCa cell lines, and to investigate whether IL-37 could be used as a radiosensitizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…One study found that although IL-37 had little direct effects on the viability of prostate cancer cells, it could increase their radiosensitivity by upregulating the expression of p27, Fas, and bax and downregulating the expression of cdk2. 78 This study suggested IL-37 as a promising radiosensitizing agent for prostate cancer therapy.…”
Section: Prostate Cancermentioning
confidence: 82%
See 1 more Smart Citation
“…One study found that although IL-37 had little direct effects on the viability of prostate cancer cells, it could increase their radiosensitivity by upregulating the expression of p27, Fas, and bax and downregulating the expression of cdk2. 78 This study suggested IL-37 as a promising radiosensitizing agent for prostate cancer therapy.…”
Section: Prostate Cancermentioning
confidence: 82%
“…However, prostate cancer cells can be radioresistant in most cases; thus, there is a strong need in finding a radiosensitizing agent for prostate cancer radiotherapy. One study found that although IL‐37 had little direct effects on the viability of prostate cancer cells, it could increase their radiosensitivity by upregulating the expression of p27, Fas, and bax and downregulating the expression of cdk2 . This study suggested IL‐37 as a promising radiosensitizing agent for prostate cancer therapy.…”
Section: Il‐37 In Tumormentioning
confidence: 94%
“…IL‐37 is a recently discovered cytokine that has been shown to play an anti‐inflammatory role in various human diseases 13 . IL‐37 could have antitumor effects in many cancer types, including fibrosarcoma, 14 breast cancer, 15 lung cancer, 16 renal cell carcinoma, 17 oral squamous cell carcinoma, 18 cervical cancer, 19 colon cancer, 20 multiple myeloma (MM), 21 prostate cancer, 22 and hepatocellular carcinoma (HCC) 23‐25 . However, the underlying mechanisms are still not fully understood 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IL-37 may become a potential biomarker and therapeutic target for male infertility. In prostate cancer, Ding VA et al [44] found that although IL-37 has no direct effect on prostate cancer, it can serve as a potential radiosensitizer. In the prostate cancer cells (DU145 cells), the proliferation of DU145 colonies was reduced by IL-37 treatment.…”
Section: Il-37 Is Helpful For Diagnosis and Therapy In Male Reproductive System Diseasesmentioning
confidence: 99%